2016
DOI: 10.4172/2155-9899.1000475
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effect of Alpha-1 Antitrypsin in Rhinovirus-infected Human Airway Epithelial Cells

Abstract: Objective Excessive airway inflammation is seen in chronic obstructive pulmonary disease (COPD) patients experiencing acute exacerbations, which are often associated with human rhinovirus (HRV) infection. Alpha-1 antitrypsin (A1AT) has anti-inflammatory function in endothelial cells and monocytes, but its anti-inflammatory effect has not been investigated in COPD airway epithelial cells. We determined A1AT’s anti-inflammatory function in COPD airway epithelial cells and the underlying mechanisms such as the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…39 Finally, in vitro models have demonstrated that a 1 -antitrypsin exerts anti-inflammatory effects in airway epithelial cells from rhinovirus-infected patients with COPD, potentially through inhibition on caspase-1 activity, suggesting a 1 -antitrypsin as a potential anti-inflammatory agent. 40 extremely narrow. Additional challenges need to be overcome, such as the structural variation of viral proteins, multiple genotypes, and high mutation rates.…”
Section: Immune and Antiviral Pathway Modulatorsmentioning
confidence: 97%
“…39 Finally, in vitro models have demonstrated that a 1 -antitrypsin exerts anti-inflammatory effects in airway epithelial cells from rhinovirus-infected patients with COPD, potentially through inhibition on caspase-1 activity, suggesting a 1 -antitrypsin as a potential anti-inflammatory agent. 40 extremely narrow. Additional challenges need to be overcome, such as the structural variation of viral proteins, multiple genotypes, and high mutation rates.…”
Section: Immune and Antiviral Pathway Modulatorsmentioning
confidence: 97%
“…In turn, A1AT treatment on infected brushed bronchial epithelial cell culture reduces viral load [34]. Moreover, A1AT administration has been proven to suppress the inflammation factors such as IL-8 in infected brushed bronchial epithelial cells and its homolog in mouse, KC (keratinocyte chemoattractant) in wild type C57BL/6 mice [35].…”
Section: A1at Utilization As a Therapeutic Agent To Overcome Infectionmentioning
confidence: 99%
“…They also imply administration of A1AT may help A1AT deficient infected patients to counteract the damage caused by the infection. HIV low level in serum precedes HIV infection; deficient patient has higher risk to get infected by HIV [13][14][15][16]; high level in serum but deficient in terms of function predisposes HIV patients with emphysema development [17] inhibits VIRIP to cleave with gp41 [28,29] Rhinovirus no reference available yet inhibits HRV receptor induction [34] and anti inflammatory [35] Dengue virus high level indicates acute phase infection [19;20,21]; higher level in DF and DHF cases compared to healthy control. A trend of higher level as the severity degree increases but not significant [26] no reference available yet…”
Section: A1at Utilization As a Therapeutic Agent To Overcome Infectionmentioning
confidence: 99%